Analisis Kegagalan Konstruksi Dan Bangunan Dari Perspektif Faktor Non Teknis - Wiyana, Yustinus Eka (Politeknik Negeri Semarang, 2012)
Construction failure is not uncommon as the construction industry is very complex, where many parties involved and processes take place in an open space. The construction failure and the building failure might be caused by either the technical or non-technical factors. The non-technical factors mostly derive from the lack of resources competence in the business entities, the employee skill, and the expertise. This paper discusses the mutual relationship between the SBU (Business Entity Competence), the SKA and the SKT (Man power Competence), and the Construction failure. This research is conducted to analyse the construction failure from the perspective of the resources competence with regard to specially the SBU, the SKA, the SKT, where as the aims of this research is to indentify the non-technical factors causing the construction failure and the building failure in Central of Jawa, and also to analyse the contributions of the SBU and the SKA and the SKT toward the Construction failure. The factors that influence the failure was measured in the qualitative model and simulated with the LPS method using the causal relationship approaches between the variables supported by the TETRAD program IV vertion 4.3.9-18. The result of the research reveals that the failure variable are structurally affected by the SBU variable 0,1181, by the SKT variable at 0,0501, and by the SKT for 0,0250. The test processes of the SBU, the SKA, and the SKT has not been implemented properly so that the certificates issue can not yet be justified. The resource conditions in the district and the city around the project area are still troublesome, such as lack of the man power having the SKT, and the SKT, and there are many skilled workers that have not got the competence test.